2018
DOI: 10.1083/jcb.201711191
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome amplification arises before neoplasia and increases upon p53 loss in tumorigenesis

Abstract: Lopes et al. examine centrosomes in human samples progressing from premalignant to metastatic lesions from patients with Barrett’s esophagus. They find that centrosome amplification can occur before transformation during human tumorigenesis, being repressed by p53, suggesting that centrosome amplification contributes to tumor initiation before p53 mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 54 publications
4
62
0
1
Order By: Relevance
“…Numeric aberrations of the centrosome and their putative link to cancer formation have long been described (3), although accurate quantifications of centriole numbers in tumor biopsies and cancer-derived cell lines have emerged only recently (9)(10)(11)(12) . To this day, the contribution of centrosomal anomalies to cancer development remain controversial, with some studies showing that higher numbers, via Plk4 overexpression, can initiate or aggravate tumorigenesis (28,29), and others showing that it is not sufficient and may even slow down progression (30,31).…”
Section: Towards Unraveling the Causes And Consequences Of Centriole mentioning
confidence: 99%
See 3 more Smart Citations
“…Numeric aberrations of the centrosome and their putative link to cancer formation have long been described (3), although accurate quantifications of centriole numbers in tumor biopsies and cancer-derived cell lines have emerged only recently (9)(10)(11)(12) . To this day, the contribution of centrosomal anomalies to cancer development remain controversial, with some studies showing that higher numbers, via Plk4 overexpression, can initiate or aggravate tumorigenesis (28,29), and others showing that it is not sufficient and may even slow down progression (30,31).…”
Section: Towards Unraveling the Causes And Consequences Of Centriole mentioning
confidence: 99%
“…In stark contrast with most proliferating cells, centriole numbers are often de-regulated during cancer development. In particular, cells with abnormally high numbers of centrioles are common in tumors and cancer-derived cell lines, and have been recently identified in pre-neoplastic tissues (8)(9)(10)(11)(12). Interestingly, within a single population of cancer cells, individual cells often carry different numbers of centrioles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that centrosome amplification occurred early in the progression of BE into EAC, and that this was dependent upon p53 loss (16). As supernumerary centrosomes can cause mitotic defects, we analyzed their presence in our BE cell lines and in the two EAC cell lines, FLO and JH-Eso-Ad1, that had the highest percentage of mitotic defects ( Fig.…”
Section: P53-deficent Be and Eac Cells Display Specific Mitotic Defectsmentioning
confidence: 97%